Online Game Addiction to Adolescent Adaptation Ability in Sikumana Village, Kupang City - Mariani Mediatrix Mone; Imelda F. E. Manurung; M. K. P. Abdi Keraf (Universitas Nusa Cendana, 2020)
Abstract. Online games are games that are accessed online by many players using the internet network. Excessive use of online games can lead to online game addiction. Teens who spend their free time playing online games have the opportunity to experience online gaming. This study aims to see the effect of online game addiction on self-efficacy in adolescents in Sikumana Village, Kupang City. The sampling technique in this study used the Slovin formula with 100 adolescents and 17-21 years old as many as subjects. This hypothesis reveals that online game addiction has a negative effect on adolescents in Sikumana Village, Kupang City. The analysis used in the study used simple regression analysis. This is indicated by a constant value of 28,432; this means that if online game addiction (X) is 0, then the self-value is 28,432. The regression coefficient for the online game addiction variable (X) is - 0.104, meaning that if online game addiction increases by 1%, then self will decrease by 0.104.